FROM RIVALS TO PARTNERS: THE EVOLUTION OF ENVIRONMENTAL COOPERATION AMONG CHINA, JAPAN, AND KOREA - Yuan, Changrui; Lee, Brice Tseen Fu (Global: Jurnal Politik Internasional, 2023)
This study analyses the trilateral cooperation among China, Japan, and Korea in the realm of environmental issues, focusing on the Trilateral Environment Ministers Meeting (TEMM) as the representative institution. Through a theoretical perspective based on rational design theory, this paper examines the rationality of TEMM's design and how it has addressed the enforcement problems and asymmetry of control among the three countries. The study also suggests some strategies for further deepening and empowering the trilateral cooperation, such as developing the environmental protection industry and carbon trading market, involving funds and non-state actors, and improving institutionalization. While acknowledging the achievements and limitations of trilateral cooperation, this paper calls for future research to employ different theories and cases to enhance our understanding of the dynamics among these three countries' cooperation.